INCONSISTENCY OF LAW ENFORCEMENT IN DISCLOSING BRIBERY IN GOVERNMENT (STUDY OF THE NORTH MALUKU NICKEL MINE CORRUPTION CASE) - Puja Rianida; Bambang Waluyo (RADJA PUBLIKA, 2025)
This study examines the inconsistency of the Corruption Eradication Commission (KPK)'s law enforcement in uncovering bribery within the government in nickel mining corruption cases. The cases addressed in this study still frequently occur within the government and are difficult to resolve due to the persistence of corruption.The current rampant cases of corruption are increasing, the perpetrators involve state officials as workers who are trusted by the public by committing abuses against applicable laws.Corruption that does not stop is like a cancer that is difficult to cure and corruption not only makes the country lose money, but also causes violations of citizens' social rights so that the crime of corruption is classified as an extraordinary crime for these reasons and circumstances.Inconsistent actions of law enforcement agencies in eradicating corruption who still selectively treat the perpetrators involved. The importance of consistent law enforcement in handling corruption cases to overcome corruption in Indonesia, but in fact, our law enforcement, one of which is the Corruption Eradication Commission (KPK), has not become a corruption eradication institution that carries out its duties properly. In the perspective of the Criminal Code and the Criminal Procedure Code, the KPK does not implement it properly as explained therein. The purpose of this study is to provide new insights to the public about inconsistent law enforcement in nickel mining licensing corruption which can be reviewed from the Criminal Code, Criminal Procedure and the negative impact of inconsistent law enforcement. The research method uses empirical normative which helps the preparation of research through interviews and legislation using qualitative methods producing descriptive analysis. The results of this study show the inconsistency of KPK law enforcement in the North Maluku nickel mining corruption and the negative impact of these inconsistent actions.